Low temperature FTIR spectroscopy and hydrogen bonding in cytosine polycrystals - Rozenberg, M. (2004)
The FTIR spectra of both the pure NH and isotopically substituted ND (<10% and>90% D) polycrystalline cytosine were recorded in the range 400-4000 cm-1 as a function of temperature (10-300 K). For the first time, uncoupled NH(D) stretching mode bands of amine and imine groups were observed in the spectra of isotopically diluted cytosine at low temperatures. These bands correspond to the three distinct H-bonds that are present in the crystal, in agreement with the available data obtained by structural methods. At least nine bands were observed below 1000 cm-1 and, in consonance with their temperature and isotopic exchange behavior, were assigned to the NH proton out-of-the-plane bending modes. Six of these bands were found to correspond to additional "disordered" H-bonds, which could not be observed by structural methods. Empirical correlations of spectral and thermodynamic parameters enabled to estimate the contribution of the H-bonds to the sublimation enthalpy of the crystal, in agreement with independent experimental data.